2020
DOI: 10.3390/met10101340
|View full text |Cite
|
Sign up to set email alerts
|

Build Size and Orientation Influence on Mechanical Properties of Powder Bed Fusion Deposited Titanium Parts

Abstract: This paper explores the influence of sample thickness and build orientation on the microstructure and mechanical properties of electron beam melting (EBM) additive manufactured Ti-6Al-4V titanium alloy and compared to previously published work on SLM-processed material. In particular, the various mechanical properties (tensile yield strength, ultimate tensile strength) were investigated with attempts to correlate with various microstructural features, including lamellae thickness, porosity and the size of prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 35 publications
(92 reference statements)
2
4
0
Order By: Relevance
“…This pronounced directional performance in additively manufactured polymer matrix composites is supported by previous publications on similar materials and is explained by the layer-wise build process as well as the alignment of reinforcement fibers in the powder spreading direction x [18][19][20][21]. The thickness dependency, which to the authors' knowledge, has been reported for various PBF materials [22][23][24][25][26][27][28][29][30][31]33,36] but not PA12 CF, revealed in the evaluated range (1-4 mm) a reduction of up to 23 and 9% for Young's modulus and Poisson's ratio, respectively (see Figure 7b). This peculiar mechanical behavior in the reference articles is typically attributed to surface roughness, internal defects and micro-structural inhomogeneity.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This pronounced directional performance in additively manufactured polymer matrix composites is supported by previous publications on similar materials and is explained by the layer-wise build process as well as the alignment of reinforcement fibers in the powder spreading direction x [18][19][20][21]. The thickness dependency, which to the authors' knowledge, has been reported for various PBF materials [22][23][24][25][26][27][28][29][30][31]33,36] but not PA12 CF, revealed in the evaluated range (1-4 mm) a reduction of up to 23 and 9% for Young's modulus and Poisson's ratio, respectively (see Figure 7b). This peculiar mechanical behavior in the reference articles is typically attributed to surface roughness, internal defects and micro-structural inhomogeneity.…”
Section: Discussionsupporting
confidence: 86%
“…The described directional behavior of PBF structures is furthermore superimposed by a severe but often overlooked thickness dependency, whereby Young’s modulus, ultimate strength and failure strain are positively correlated to part thickness. Due to the relevancy for lightweight design that relies on the utilization of thin structural members, this effect has recently gained more attention and was reported in a multitude of studies for metal- [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ] as well as polymer-based PBF [ 29 , 30 , 31 ] and other processes like fused deposition modeling [ 32 ] and material jetting [ 33 ]. It appears plausible that the behavior is likewise inherent in laser-sintered short-fiber-reinforced polymers; however, no published articles were found addressing this issue.…”
Section: Introductionmentioning
confidence: 99%
“…The versatility of SLM has attracted significant interest in manufacturing high-value alloys used in aerospace, automobile and biomedical applications [2,3]. A wide range of SLMfabricated alloys has been investigated, such as titanium alloys [4,5], aluminum alloys [6,7] and steels [8,9], with emphasis on processing parameter optimization, microstructure manipulation and mechanical properties improvement.…”
Section: Introductionmentioning
confidence: 99%
“…The imperfections, which can occur during such complex AM processes, namely pores, part distortion, or lack of fusion defects, should not also be neglected in the design process [ 2 ] but they also cannot be predicted explicitly. It has been shown in numerous studies that the properties of AM products largely depend on the orientation of the structure during the manufacturing process, size of the structure, or set of process parameters [ 3 ]. In addition, each AM method has its specifics, which makes it difficult to transfer knowledge between them [ 4 ].…”
Section: Introductionmentioning
confidence: 99%